Future Trends of democracy in the Middle East By 2025 and its effect on the national interests of the Islamic Republic of IranFuture Trends of democracy in the Middle East By 2025 and its effect on the national interests of the Islamic Republic of Iran - mojtaba shariati (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2018)
The Middle East is changing. More actors and factors also influenced its changes, which has added to the complexity of the issues.These undetermined and vague conditions have led to different scenarios, which could figure out the future of the Islamic countries and the Middle East in general. So in this article, this main question is answered, future trends of democracy in the Middle East by 2025, will have what effects on the national interests of the Islamic Republic of Iran?.In response to the main question, by reviewing the future study of future trends of democracy in the Middle East, a questionnaire was designed within the framework of the theory of constructivism and Delphi method, and was distributed among of experts and specialists. Then, by guiding with leadership team, the Delphi questionnaire data were analyzed. Then the results and opinions of the experts and respondents to the questions were analyzed qualitatively and four main scenarios were obtained which includes the rule of religious democracy, secularism, Salafism and the military, autocratic monarchy and ethnic governments.Finally, the most favorable scenario and the most threatening scenario for the national interests of the Islamic Republic of Iran were detected and solutions presented.